2020
DOI: 10.1371/journal.pone.0236596
|View full text |Cite
|
Sign up to set email alerts
|

Fragile neutrophils in surgical patients: A phenomenon associated with critical illness

Abstract: Leukocyte viability (determined by e.g. propidium iodide [PI] staining) is automatically measured by hematology analyzers to check for delayed bench time. Incidental findings in fresh blood samples revealed the existence of leukocytes with decreased viability in critically ill surgical patients. Not much is known about these cells and their functional and/or clinical implications. Therefore, we investigated the incidence of decreased leukocyte viability, the implications for leukocyte functioning and its relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…7 The pathophysiology of ARDS is normally mediated by malfunctioning of the neutrophil compartment leading to accumulation and specific activation of these cells in the pulmonary tissue, which in turn causes collateral damage characterized by destruction of epithelial and endothelial cells. [8][9][10][11][12] Tissue damage is caused by neutrophil-driven mechanisms that are normally employed to kill microorganisms, which include production of reactive oxygen species, degranulation of toxic proteins and enzymes, and netosis. 10,13,14 This leads to increased vascular permeability and protein-rich alveolar edema causing decreased gas exchange and hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The pathophysiology of ARDS is normally mediated by malfunctioning of the neutrophil compartment leading to accumulation and specific activation of these cells in the pulmonary tissue, which in turn causes collateral damage characterized by destruction of epithelial and endothelial cells. [8][9][10][11][12] Tissue damage is caused by neutrophil-driven mechanisms that are normally employed to kill microorganisms, which include production of reactive oxygen species, degranulation of toxic proteins and enzymes, and netosis. 10,13,14 This leads to increased vascular permeability and protein-rich alveolar edema causing decreased gas exchange and hypoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…The ARDS found in COVID‐19 patients is characterized by decreased oxygenation and rapid respiratory failure 7 . The pathophysiology of ARDS is normally mediated by malfunctioning of the neutrophil compartment leading to accumulation and specific activation of these cells in the pulmonary tissue, which in turn causes collateral damage characterized by destruction of epithelial and endothelial cells 8–12 . Tissue damage is caused by neutrophil‐driven mechanisms that are normally employed to kill microorganisms, which include production of reactive oxygen species, degranulation of toxic proteins and enzymes, and netosis 10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune system demonstrates the most pronounced changes after prolonged exercise 17 . The primary effector cells of the innate immune system are granulocytes and monocytes 21–23 . Receptor expression on these cells, measured by flow cytometry, has proven to give insight into the status of the innate immune system 24–26 …”
Section: Introductionmentioning
confidence: 99%
“…17 The primary effector cells of the innate immune system are granulocytes and monocytes. [21][22][23] Receptor expression on these cells, measured by flow cytometry, has proven to give insight into the status of the innate immune system. [24][25][26] A recent study showed that intensive exercise led to the mobilization of neutrophil phenotypes associated with systemic inflammation and immunosuppression.…”
mentioning
confidence: 99%
“…However, small and large subpopulations of monocytes have recently been described in peripheral blood in healthy state, with classical CD16monocytes comprising the majority of populations of both sizes, and cell-size dependent responses to stimulation within donors, which supports size differences being an actual phenotype unlinked to cell death 38 . In addition, the neutrophil fraction, which is the most delicate leukocyte cell subtype with high sensitivity to shear stress and temperature changes, did not present a significant variation in size between tissues, casting doubt on apoptosis being the cause for all observed cell shrinkage 39,40 . Differential isotonic pressure of tissue significantly impacts the size of leukocytes, which may be an alternative explanation for size differences observed as breastmilk has higher osmolality than peripheral blood 41,42 .…”
Section: Major Phenotypic Changes Are Observed In Leukocyte Subpopulations Between Investigated Tissuesmentioning
confidence: 98%